HUBUNGAN KONSENTRASI BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS IV SDN 1 SINGKAWANG - Mapiansyah; Emi Sulistri; Rosmaiyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study was motivated by the low level of achievement in mathematics learning of students based on the results of the odd semester Final Assessment (PAS) for the 2023-2024 school year, where 50% of students did not reach the minimum score (KKM). This study aims to determine whether there is a relationship between learning concentration and mathematics achievement of fourth-graders at SDN 1 Singkawang. The research method used is correlational research with a quantitative approach. The object of this research is 77 fourth-graders at SDN 1 Singkawang. Data collection was carried out using student learning concentration questionnaires and documentation of student mathematics report scores for the 2023/2024 school year. The data were analyzed using descriptive statistics, testing the requirements of the analysis using normality tests with the Kolmogorov-Smirnov test formula and linearity tests. Hypothesis testing was carried out using the Pearson Product Moment correlation test. The results of the analysis showed that there was a significant relationship between learning concentration and mathematics achievement of fourth-graders at SDN 1 Singkawang, which was indicated by a correlation value of 0.51, which means it has a sufficient criterion based on the level of correlation, so that the relationship is not too strong. Learning concentration is one of the factors that influences students' mathematics achievement, with a contribution of 25.63%. This is indicated by the value of the coefficient of determination (KD) of 25.63%, which means that the magnitude of the relationship between learning concentration and students' mathematics achievement is 25.63%.